Perancangan Sistem Pendeteksi Asap Dan Monitoring Kelembaban Suhu Pada Ruang Server Berbasis Internet Of Things Menggunakan Metode Fuzzy Logic Studi Kasus : Ruang Server Yby.Net - Muhamad Supriyanto; Fajar Agung Nugroho (STIE AUB Surakarta, 2022)
In a server room, temperature and humidity settings are very important. In order to keep the server operating properly, some adequate maintenance and security efforts are required such as monitoring the server. The server room environment needs to be monitored as it relates directly to the server hardware and can affect its performance. Due to the limited ability of human resources in monitoring the server, a support system is needed that is always active, connected, and working continuously, based on the Internet of Things (IoT). With advances in technology and IoT now, it is possible to check the temperature and humidity and detect the smoke of a room without having to look at the monitor of the measuring instrument in the room. Information and monitoring results of DHT22 and MQ2 can be viewed directly through the website that has been created which displays data in real time. With the help of the NodeMCU Esp8266 microcontroller. In making this tool, several methods are used including collection and literature, component testing, system testing that has been designed and made so that the end result of this observation is that the website can store temperature and humidity data, automatically so that the data can be accessed in the future and can be analyzed automatically. direct. The objectives of this research are, To make a smoke detector and monitoring temperature and humidity using DHT-22 sensor and MQ-2 sensor based on internet of things, Can monitor temperature and humidity and detect smoke, Can store temperature and temperature measurement data humidity into the database, Reception of temperature and humidity and smoke detectors to the web every 5 minutes, This research was conducted to improve time efficiency. Based on the results of research on the manufacture of smoke detection systems and monitoring of temperature and humidity in server rooms, a tool is produced that can help administrators to monitor server rooms remotely. After the results of the research, it can be concluded that prototype of the smoke detection and monitoring system of the server room can function properly so that it can assist in monitoring, the prototype of the room security system can help to minimize the occurrence of overhead on the server and cause smoke, because in the system there are DHT22 sensors for temperature and humidity as well as MQ2 sensors to detect smoke, Monitoring Website can assist administrators or users in obtaining information about monitoring results from the tool remotely